Multivariate Analysis Model in Measuring the Level of the Efficiency Islamic Banking Industry - Kusumo, Willyanto Kartiko; Muljono, Muljono (Economics and Business Solutions Journal, 2019)
Efficiency is one of the performance parameters underlying an organization. Efficiency in the world of banking is one of the performance parameters that is quite popular and widely used because it is the answer to the difficulties in calculating banking performance measurements. The measurement of banking efficiency can be done with Multivariate Analysis. Multiveriate is a methodology for determining relative efficiency and managerial performance based on empirical data. In this method, profit is modeled to be deviated from its profit efficient frontier which is influenced by the input and output functions. The sample of this study was 40 Islamic Commercial Banks and Islamic Business Units for 4 years starting from 2014-2018 which were analyzed using the STATA 8 technique with panel data. The results of this research show that Islamic banks are technically efficient based on intermediation (100%) and the efficient scale based on intermediation and production. Efficiency can be increasing liquid assets, while based on production approach.